Disaster Risk Reduction for Resilience Climate Change and Disaster Risk Adaptation - Rivera Arriaga, Evelia; Silva, Rodolfo; Cruz Ramírez, Cesia; Azuz-Adeath, Isaac; Vega-Serratos, Beatriz E.; Posada Vanegas, Gregoria (Springer, 2023)
The climate system tends to respond to changes in a gradual way until it crosses some threshold; thereafter, any change defined as abrupt is one where the response is much greater than the change in the perturbing force. Improving resilience to the extreme events caused by climate change has become an important issue, and links between factors such as demographics, climate change effects, water and food availability and supply, governability and violence, risk and vulnerability, economic and ecological crises, and health and sanitation have gained importance in the global context. Coastal governance involves economic, social, environmental, institutional, cultural, traditional, and political entities, and it can be viewed as a combination of shared government, in which society also assumes the legitimacy of the process and the recognition of the decisions made. The difference of considering governance for climate change-related effects beyond thinking about governance for anything else is the resilience for long-term, uncertain futures. According to the IPCC (2014), resilience is the ability of a system to anticipate, absorb, and adapt to climate-related shocks and stresses and to respond in ways that preserve, restore, or improve its essential functions, structures, and identity. This chapter is focused on improving the resilience of the 11,600 km of the Mexican coastline to abrupt climate changes. This study identifies the areas most at risk, based on an evaluation of the hazards they face and their degree of vulnerability. The elevations, geology, geomorphology and displacement of the coastline, significant wave heights, tidal range, the level of natural protection, hazards induced from extreme waves and storm surge, and rainfall were included in the risk analysis. Socioeconomic characteristics, such as total population, population density, GDP per capita, economic participation rate, human development index, marginalization index, poverty, economic units (tourism), total gross production, gross value added (tourism), protected areas, and productive sectors were used to evaluate social vulnerability.
Risk Management of Extreme Precipitation in Mexico: Building Resilience
Keywords: Resilience; Extreme rain; Governance; Risk management; Vulnerability index; Campus Ensenada